2013
DOI: 10.1089/bio.2012.0049
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a Frozen Sample Aliquotter to Prepare Plasma and Serum Aliquots Without Thawing Frozen Parent Samples

Abstract: Human biospecimens represent invaluable resources to advance molecular medicine, epidemiology, and biomarker discovery/validation, among other biomedical research. Biobanks typically cryopreserve biospecimens to safeguard their biochemical composition. However, exposing specimens repeatedly to freeze/thaw cycles can degrade their integrity in unforeseen ways. Those biobanks storing liquid samples, thus, regularly make a fundamental compromise at collection time between freezing samples in many small volumes (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Many authors have repeatedly stated that a majority of low abundance and/or low molecular weight proteins deteriorate either in quality or quantity or both upon repeated freeze-thaw cycles which for some proteins(such as VEGF) is as low as 1 F/T cycle [50]. The ideal practice to avoid sample stability issues is to make one time use aliquots of the total sample volume and prevent repeated freeze thaw cycles of the entire sample quantum [50]. Even these aliquots should be thawed on ice to prevent any damage to the sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have repeatedly stated that a majority of low abundance and/or low molecular weight proteins deteriorate either in quality or quantity or both upon repeated freeze-thaw cycles which for some proteins(such as VEGF) is as low as 1 F/T cycle [50]. The ideal practice to avoid sample stability issues is to make one time use aliquots of the total sample volume and prevent repeated freeze thaw cycles of the entire sample quantum [50]. Even these aliquots should be thawed on ice to prevent any damage to the sample.…”
Section: Resultsmentioning
confidence: 99%
“…In such cases samples should be immediately snap frozen in liquid nitrogen and sealed in a sterile cryocans [50]. In any case the sample must finally be kept at -80 ˚C or liquid nitrogen for long term storage.…”
Section: Resultsmentioning
confidence: 99%
“…For cryopreservation, dimethyl sulfoxide (DMSO) is added to cells as a cryoprotectant, and samples are stored in liquid nitrogen vapor to prevent cell death (Holland et al 2005;Vaught 2006). Ellis and Venturini (2013) also showed that blood samples may be frozen in larger volumes and that frozen aliquots removed from the stock solution without thawing the samples and without a significant loss in sample integrity, thereby decreasing the number of sample tubes needed to store multiple aliquots. While high levels of reproducibility were observed for cholesterol, triglycerides, glucose, and immunoglobulin G, the effectiveness of this technique for other analytes in blood may vary (Ellis and Venturini 2013).…”
Section: Blood Biomarkers: Environmental Applications Blood Compositimentioning
confidence: 99%
“…Ellis and Venturini (2013) also showed that blood samples may be frozen in larger volumes and that frozen aliquots removed from the stock solution without thawing the samples and without a significant loss in sample integrity, thereby decreasing the number of sample tubes needed to store multiple aliquots. While high levels of reproducibility were observed for cholesterol, triglycerides, glucose, and immunoglobulin G, the effectiveness of this technique for other analytes in blood may vary (Ellis and Venturini 2013). Blood samples are commonly stored in biorepositories, such as the European Cancer Study biorepository, which contains more than 380,000 blood samples.…”
Section: Blood Biomarkers: Environmental Applications Blood Compositimentioning
confidence: 99%